RENEWABLE ENERGY BASED FAULT IDENTIFICATION IN A IEEE15 BUS DISTRIBUTION NETWORK - Syed Abdul Mujeer, Sapireddy Venkata Santosh Kumar (International Journal of Control and Automation, 2020)
In this paper new issue area strategy by utilizing spiral premise work neural system (RBFNN) for a conveyance coordinate with DGs has introduced. The two stage flows of one end are taken as contributions to the proposed conspire. The recommended approach can decide the precise kind and area of flaws utilizing RBF neural system. A few contextual analyses have been made to confirm the precision of the proposed technique for shortcoming finding in a circulation framework with DGs utilizing a MATLAB. Results indicated that the proposed strategy can precisely decide the area of shortcomings in a dissemination framework with a few DG units.